Incorporating Multicultural Couple and Family Therapy Into Incarcerated Settings - Tadros, Eman (International journal of offender therapy and comparative criminology, 2019)
Incarceration rates have increased significantly since the 1990s, with more than two million adults in federal, state, and local facilities. More than half of the offenders report a history of mental health issues, highlighting the importance of offenders having access to effective therapeutic approaches, including individual, couples, and family counseling. Traditionally, the focus of mental health services has been individual treatment; however, family members are also significantly impacted by the offender's absence during incarceration. Incorporating family members into treatment can serve to improve relationships, leading to better outcomes at reentry and reductions in recidivism rates. Given the preponderance of persons of color in the incarcerated population, diversity issues in counseling must also be addressed. The purpose of the underlined article is to explore the implications of incorporating multicultural family therapy into incarcerated settings.